Empathy Training Based on the Culture of Peace in Makassar Bugis Towards the Improvement of Peaceful Personalities - Zakina, Nurul; Buchori, Sahril; Amirullah, M (Konseling Edukasi : Journal of Guidance and Counseling, 2026)
Empathy training based on bugis makassar peaceful culture to improve students' peaceful personality. This study examines the effect of Empathy training technique based on Bugis Makassar peaceful culture on improving students' peaceful personality. The issue addressed is students' low peaceful personality characterized by inability to forgive, weak emotional control, and lack of empathy. The research novelty lies in integrating Bugis Makassar local wisdom Sipakatau, Sipakainge', and Sipakalebbi into empathy training. Using quasi-experimental design, 18 seventh-grade students were divided into experimental and control groups. Intervention was conducted through group counseling integrating three cultural values. Data were collected using peaceful personality scale and analyzed statistically. Results showed experimental group experienced highly significant improvement from low to high category, while control group remained unchanged. This culturally-based technique provides school counselors an alternative approach to enhance students' peaceful personality and prevent conflicts. The research significance highlights the importance of integrating local wisdom into guidance and counseling curriculum for meaningful character education.Keywords: Empathy Training; Peaceful Personality; Bugis Makassar Local Wisdom